A Conceptual Paradigm and Approach for the Study of Innovators - Bigoness, William J.; Perreault, William D. (Academy of Management Journal, 1981)
An operational approach for measuring an organization's innovativeness is proposed. This procedure draws on measurement theory to overcome problems often associated with single product and composite measures of innovativeness. A criterion variable is used to test the relationship between selected organizational characteristics and firm innovativeness. Firms possessing internal technical expertise were found to be more innovative than firms without such expertise.